Alteridades que nos rescatan de lo uniforme: ¿cómo escapar de un mundo de iguales? - Bard Wigdor, Gabriela (CIICLA, Universidad de Costa Rica, 2019)
This essay is the outcome of years of personal exploration as a feminist researcher and a result of a collective challenge among peers, to generate knowledge that contributes to processes of emancipation of the most vulnerable sectors of the system and to glimpse that the deepest transformations we have not achieved. Impotence gave way to frustration and later to the revelation that no change is possible without first transforming one's own oppressive paradigms and lifestyles. By means of this writing, I intend to reflect on my own processes of epistemic surveillance and collective bets for transforming reality, the structural conditioning that produces fatigue and depression that respond to an essentially productivist capitalist order. I also want to discuss theories and methodologies we use to generate emancipatory knowledge and then to address the final reflection, where I attempt, from a decolonial feminist approach, to define love both as affection and as a lasting link with the people we consider alterities, so far as they are those who can save us from the uncritical reproduction of knowledge and isolation to which the capitalist cishetero-patriarchal society subjects us.